(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teaching specialized vocabulary in the context of English for Specific Purposes (ESP) is a crucial aspect of university-level English language instruction. The aim of ESP courses is to equip university students with the skills needed to communicate effectively in their future workplaces and during clinical practice abroad. The first section of this paper offers a theoretical foundation for a range of exercises focused on teaching Medical English. In the second section, the authors share examples of activities they designed and implemented in their ESP classes. These exercises are effective in aiding students’ acquisition and long-term retention of scientific vocabulary pertinent to their fields of study.